دور إدارة الموارد البشرية الخضراء في تحسين الأداء البيئي في المؤسسات الإستشفائية - ين عطية, فتيحة (My University, 2022)
The future of humanity is closely related to the extent of the ability of current generations to preserve the environment and holds them responsible for delivering a clean and green environment for future generations, and since the health sector is one of the important sectors in this scope, the great role that individuals play in the application in this field and its impact on environmental performance . The study aims to highlight the role of green human resources management in improving the environmental performance of hospital institutions. A case study was conducted: The University Hospital Center in Mostaganem through a questionnaire distributed to (66) employees. The data was analyzed using the Statistical Packages Program for Social Sciences ( Statistical Package for Social Science )( SPSS 20 ) . The results of the study confirmed the existence of a statistically significant relationship between the dimensions of green human resource management and environmental performance improvement. These dimensions include green employment, green training, green performance assessment and green integration, and therefore focus must be placed on adopting appropriate policies and strategies for managing green human resources and applying these policies. On the ground and changing the culture o
المركز الإستشفائي الجامعي مستغانم
Keywords: الموارد البشرية الخضراء - تحسين الأداء البيئي- المشؤولية الإجتماعية